Next-Generation Sequencing for Whole-Genome Characterization of Weissella cibaria UTNGt21O Strain Originated From Wild Solanum quitoense Lam. Fruits: An Atlas of Metabolites With Biotechnological Significance - Tenea, Gabriela N.; Hurtado, Pamela (Frontiers in Microbiology, 2021)
The whole genome of Weissella cibaria strain UTNGt21O isolated from wild fruits of Solanum quitoense (naranjilla) shrub was sequenced and annotated. The similarity proportions based on the genus level, as a result of the best hits for the entire contig, were 54.84% with Weissella, 6.45% with Leuconostoc, 3.23% with Lactococcus, and 35.48% no match. The closest genome was W. cibaria SP7 (GCF_004521965.1) with 86.21% average nucleotide identity (ANI) and 3.2% alignment coverage. The genome contains 1,867 protein-coding genes, among which 1,620 were assigned with the EggNOG database. On the basis of the results, 438 proteins were classified with unknown function from which 247 new hypothetical proteins have no match in the nucleotide Basic Local Alignment Search Tool (BLASTN) database. It also contains 78 tRNAs, six copies of 5S rRNA, one copy of 16S rRNA, one copy of 23S rRNA, and one copy of tmRNA. The W. cibaria UTNGt21O strain harbors several genes responsible for carbohydrate metabolism, cellular process, general stress responses, cofactors, and vitamins, conferring probiotic features. A pangenome analysis indicated the presence of various strain-specific genes encoded for proteins responsible for the defense mechanisms as well as gene encoded for enzymes with biotechnological value, such as penicillin acylase and folates; thus, W. cibaria exhibited high genetic diversity. The genome characterization indicated the presence of a putative CRISPR-Cas array and five prophage regions and the absence of acquired antibiotic resistance genes, virulence, and pathogenic factors; thus, UTNGt21O might be considered a safe strain. Besides, the interaction between the peptide extracts from UTNGt21O and Staphylococcus aureus results in cell death caused by the target cell integrity loss and the release of aromatic molecules from the cytoplasm. The results indicated that W. cibaria UTNGt21O can be considered a beneficial strain to be further exploited for developing novel antimicrobials and probiotic products with improved technological characteristics.